Estudo de parâmetros reacionais em moinho de bolas na síntese de aril(heteroaril)-1h-pirazóis - Paveglio, Guilherme Caneppele (2012)
This paper describes a study of reaction parameters in a ball mill in the synthesis of 1H-pyrazole acid catalyzed. The studied parameters were: amount of reactants, frequency, reaction time, amount of catalyst, number of milling balls, different catalysts, diameter and material of the milling balls. Another study was conducted to study the mechanism of solid-solid reaction involved in the cyclocondensation between enaminones and hydrazine hydrochloride acid catalyzed. These mixtures were studied by thermal analysis (TGA and DSC), where eight enaminones were evaluated and four eutectic mixtures were identified.